ONLINE ENGINEERING EDUCATION: LEARNING ANYWHERE, ANYTIME - Bourne, John; Harris, Dale; Mayadas, Frank (Online Learning, 2005)
The emergence of worldwide communications networks and powerful computer technologies has redefined the concept of distance learning and the delivery of engineering education content. This article discusses the Sloan Consortium’s quest for quality, scale, and breadth in online learning, the impact on both continuing education of graduate engineers as well as degree-seeking engineering students, and the future of engineering colleges and schools as worldwide providers of engineering education.